2007
DOI: 10.3201/eid1308.070393
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza (H5N1) Susceptibility and Receptors in Dogs

Abstract: Inoculation of influenza (H5N1) into beagles resulted in virus excretion and rapid seroconversion with no disease. Binding studies that used labeled influenza (H5N1) showed virus attachment to higher and lower respiratory tract tissues. Thus, dogs that are subclinically infected with influenza (H5N1) may contribute to virus spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…Serological studies 11,[15][16][17]21,23 of influenza A exposure in dogs have been conducted by means of enzyme-linked immunosorbent assay (ELISA) and/or hemagglutination inhibition (HI) assay as screening and confirmatory tests, respectively. The sensitivity (Se) and specificity (Sp) of these assays under unknown field conditions have not been reported for canine sera.…”
Section: Introductionmentioning
confidence: 99%
“…Serological studies 11,[15][16][17]21,23 of influenza A exposure in dogs have been conducted by means of enzyme-linked immunosorbent assay (ELISA) and/or hemagglutination inhibition (HI) assay as screening and confirmatory tests, respectively. The sensitivity (Se) and specificity (Sp) of these assays under unknown field conditions have not been reported for canine sera.…”
Section: Introductionmentioning
confidence: 99%
“…BJ94-like GD/V H9N2 virus is avian-origin influenza and the H9N2 virus can robustly stimulate Type I and Type III interferon (IFN) expression (Sutejo et al, 2012), which may relate to the mild effect in inoculated beagles. For virus, the distinct characterization of the different H9N2 strains could cause the varying replication in dogs, as seen in previous studies on H5N1in dogs (Chen et al, 2010;Giese et al, 2008;Maas et al, 2007). Influenza A virus has a RNA-dependent RNA polymerase constituted from PA (polymerase acidic), PB1 (polymerase basic 1) and PB2 (polymerase basic 2) subunits and assembled with nucleoproteins (NP) and a viral RNA (vRNA), forming a viral ribonucleoprotein (RNP) complex in the host nucleus (Neumann et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…However, recent studies have reported that infection and transmission efficiency of H5N1 viruses in dogs are low, and heavy exposure is required for H5N1 viruses to establish canine infection. 8,19 In contrast, the equine-derived H3N8 virus is efficiently transmitted to dogs. Since 2004, many states in the USA have reported canine influenza cases, although these outbreaks are usually sporadic and self-limiting.…”
Section: Highly Pathogenic Avian Influenza Virusesmentioning
confidence: 99%